Wealth of wisdom : the top 50 questions wealthy families ask - McCullough, Tom (Financial planner); Whitaker, Albert Keith (Gildan, 2019)
Managing significant wealth is a complex affair, and navigating the financial world at that level involves making decisions that can have major ramifications--these are not decisions to make lightly. This book equips you to take positive action, be proactive, and make the tough decisions to protect and grow your family's wealth.